Peritonitis and splenitis caused by MAC-infection in an immunosuppressed patient - D. V. Plotkin; M. N. Reshetnikov; M. V. Sinitsyn; Yu. R. Zyuzya (Журнал инфектологии)
Primary (hematogenic) peritonitis caused by non-tuberculosis mycobacteria is extremely rare in the clinical practice. The main number of reported episodes of primary intraabdominal infection is associated with M. tuberculosis and the development of granulomatous inflammation of the peritoneum visually similar to carcinomatosis. The vast majority of reports of peritonitis associated with non-tuberculosis mycobacteria are interlinked with chronic peritoneal dialysis or foreign bodies of the abdominal cavity, when an infection is carried out by the contact through a dialysis catheter, prosthesis or a gastric banding device. The article describes a clinical case of peritonitis and splenitis caused by M. avium with hematogenic spread of infection from the primary pulmonary focus in a young patient with immunosuppression. Diagnosis of such peritonitis at the preoperative stage is extremely difficult due to the similarity of symptoms with atypical appendicitis or infected ascites. The intraoperative picture also did not allow us to assume a mycobacterial etiology of the process, and the absence of a focal point of peritonitis made it necessary to thoroughly understand the situation. Only a peritoneal biopsy and a complete laboratory examination of exudate allowed us to verify the diagnosis, to understand the pathogenetic mechanisms of the disease and to start a timely etiotropic therapy.